GA based static scheduling of multilevel assembly job shops. (21st January 2009) - Omkumar, M.; Shahabudeen, P.; Gughan, S.; Azad, A.
This research focuses on scheduling operations of multi-level jobs, which undergo serial, parallel, and assembly operations in static assembly job shops with an objective of minimising makespan. A new optimisation heuristic based on Genetic Algorithm (GA) is proposed. Its performance is compared with some of the dispatch rules, which have best performances in scheduling multilevel jobs in dynamic assembly job shop. A simulation of assembly job shop is developed and integrated with a GA heuristic routine and analysed. It is found that the proposed algorithm performs well with respect to minimising the makespan compared to other dispatch rules.